Simultaneous deep transcriptome and proteome profiling in a single mouse oocyte - Yi-Rong Jiang; Le Zhu; Lan-Rui Cao; Qiong Wu; Jian-Bo Chen; Yu Wang; Jie Wu; Tian-Yu Zhang; Zhao-Lun Wang; Zhi-Ying Guan; Qin-Qin Xu; Qian-Xi Fan; et al. (Cell Reports, 2023)
Summary: Although single-cell multi-omics technologies are undergoing rapid development, simultaneous transcriptome and proteome analysis of a single-cell individual still faces great challenges. Here, we developed a single-cell simultaneous transcriptome and proteome (scSTAP) analysis platform based on microfluidics, high-throughput sequencing, and mass spectrometry technology to achieve deep and joint quantitative analysis of transcriptome and proteome at the single-cell level, providing an important resource for understanding the relationship between transcription and translation in cells. This platform was applied to analyze single mouse oocytes at different meiotic maturation stages, reaching an average quantification depth of 19,948 genes and 2,663 protein groups in single mouse oocytes. In particular, we analyzed the correlation of individual RNA and protein pairs, as well as the meiosis regulatory network with unprecedented depth, and identified 30 transcript-protein pairs as specific oocyte maturational signatures, which could be productive for exploring transcriptional and translational regulatory features during oocyte meiosis.